What drives income inequality? Bayesian evidence from the emerging market economies - Shengquan Wang; Yuan Gao; Mingjin Luo (Journal of Applied Economics, 2023)
What drives income inequality in emerging market economies? To end it, we approach this topic utilizing Bayesian model averaging and 27 emerging market economies panel dataset from 1990 to 2019. First, differently, we find a U-shaped Kuznets curve in emerging market economies rather than the notable inverted U-shaped curve. Besides, we find four strictly robust determinants of income inequality in emerging market economies, including the population aging, the female labor force participation, the unemployment level and the share of labor compensation in output. These results remain stable through a series of robustness checks. In most cases, the government expenditure and real exchange rate could also robustly drive the dynamics of income inequality in emerging market economies. Further, a comparative analysis suggests that financial development, inflation, human capital condition, total factor productivity and urbanization are distinct determinants of income inequality in the market economies.
Keywords: 330; Bayesian model averaging; drivers; emerging market economies; Income inequality